Genome-Wide Identification and Evolutionary Analysis of the SnRK2 Gene Family in Nicotiana Species - Yu Tang; Yangxin Zhang; Zhengrong Hu; Xuebing Yan; Risheng Hu; Jibiao Fan (Agriculture, 2025)
Soil salinization threatens agriculture by inducing osmotic stress, ion toxicity, and oxidative damage. SnRK2 genes are involved in plant stress responses, but their roles in salt stress response regulation of tobacco remain unclear. Through genome-wide analysis, we identified 54 SnRK2 genes across four Nicotiana species (N. tabacum, N. benthamiana, N. sylvestris, and N. tomentosiformis). Phylogenetic reconstruction clustered these genes into five divergent groups, revealing lineage-specific expansion in diploid progenitors (N. tomentosiformis) versus polyploidy-driven gene loss in N. tabacum. In silico promoter analysis uncovered regulatory networks involving light, hormones, stress, and developmental signals, with prevalent ABA-responsive elements (ABREs) supporting conserved stress-adaptive roles. Structural analysis highlighted functional diversification through variations in intron–exon architecture and conserved kinase motifs. This study provides a genomic atlas of SnRK2 evolution in Nicotiana, offering a foundation for engineering salt-tolerant crops.